Discourse on Ethnic Discrimination: A Critical Discoure Analysis of Political Statements Presented by The Members of Indonesia House of Representative in Social Media - Siska Cicilia; Andi Muhammad Irawan (English Language and Literature, 2023)
This study examines the discriminatory discourse contained in the statements of members of the Indonesian Council which is addressed to ethnicity. This study aims to reveal the topics of discourse presented and the discourse strategies used by council members in their tweets and speeches when presenting ethnic minorities negatively. The type of research used in this research is descriptive qualitative research. The results of this study based on Youtube found 28 racist statements. Then, Twitter found 10 tweets. And Instagram found 15 statements. The theoretical framework of critical discourse analysis (CDA) used in this study is based on Van Dijk's 'ideological square', namely positive self-presentation and other negative presentations. From the discriminatory discourse analysis posed by the council members, it was found that 10 statements were categorized as problematization strategy, 1 statement categorized as blaming the victim (scapegoating), 4 statements categorized as metaphor, 14 statements categorized as prejudice strategy, 22 statements categorized as negative attribution, and 2 statements are categorized in disclaimers.